Effect of nitrogen fertilization and Salicylic acid on some morphological and physiological traits Of coriander plant ( Coriandrum sativum L.) - عبدالعزيز, محمد; درويش , مجد; غانم, علاء (Latakia University Journal -Biological Sciences Series, 2021)
The research was conducted during the agricultural season 2019 in the Syrian coast in Tartous governorate, the village of Beit Sheikh Yunus. The experiment was designed in a Randomized Complete Block design( R.C.B.D) with a split plot arrangement of treatments with three replicates for each treatment . To study the effect of nitrogen fertilization and Salicylic acid on some morphological(Plant height cm,leg diameter at root knot, number of main branches/plant, number of leaves/plant) and physiological (Leaves surface area cm2, Leaves area guide) traits of coriander (Coriandrum sativum .L). In this study, four nitrogen fertilization rates )F1=0 ،F2=60 ،F3=100، F4=140) kg/h and three Salicylic acid concentrations (S1=0، S2=20، S3=4) mlg/L were used . The study showed following results: The nitrogen fertilization rate (F3)achieved a significant superiority over the tow rates (F1, F2) and was not significant over the rate(F4)in all morphological and physiological characteristics, also spraying with Salicylic acid (S3) gave a significant increase to the tow concentration (S1,S2)in all the studied traits. The interaction between nitrogen fertilization rate (F3)and spraying with Salicylic acid (S3) gave the best values in all studied morphologica and physiological traits as the height of the plant reached (85.94)cm and the area of the leaf surface reached (851.20) cm2.